2018
DOI: 10.1186/s12957-018-1361-2
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinoscopy-assisted esophagectomy for T2 middle and lower thoracic esophageal squamous cell carcinoma patients

Abstract: BackgroundWe aimed to compare mediastinoscopy-assisted esophagectomy (MAE) with the Ivor Lewis procedure in T2 middle and lower thoracic esophageal carcinoma patients in fields of perioperative complications and overall survival (OS).MethodsThe clinical data of 112 T2 esophageal cancer patients who received MAE (n = 31) or Ivor Lewis procedure (n = 81) from January 2010 to December 2015 were retrospectively analyzed in propensity score analysis. Thirty-eight T2 esophageal cancer patients who underwent MAE (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…Although published reports had compared the 2 surgical methods, the best surgical method for treating esophageal cancer was still considerably controversial. Those published studies 3,6,10 had a different focus, and several of them did not conduct survival analysis. Our study comprehensively compared the intraoperative, postoperative, and survival outcomes of MATHE and TATTE.…”
Section: Discussionmentioning
confidence: 99%
“…Although published reports had compared the 2 surgical methods, the best surgical method for treating esophageal cancer was still considerably controversial. Those published studies 3,6,10 had a different focus, and several of them did not conduct survival analysis. Our study comprehensively compared the intraoperative, postoperative, and survival outcomes of MATHE and TATTE.…”
Section: Discussionmentioning
confidence: 99%
“…9 In a similar study in 2004, 42 esophageal cancer patients underwent MAE and the results showed less bleeding during surgery, shorter duration of surgery, and the possibility of greater lymph node resection. 10 Wang and colleagues 11 operated on 112 T2 stage esophageal cancer patients, using Ivor Lewis esophagectomy (81 patients) and mediastinoscope-assisted esophagectomy (31 patients). The duration of surgery and intraoperative blood loss in the MAE method were less than in the Ivor Lewis method, but patient survival did not depend on the surgical method and the involvement of the lymph nodes was more effective.…”
Section: Discussionmentioning
confidence: 99%
“…The stomach is fixed to the left thorax in the Sweet procedure, but to the right thorax in the Ivor-Lewis procedure. [9] Fixing the stomach to the right thorax induces an inappropriate angle between the pyloric region and stomach; [6] this may explain for the delay in gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…The Ivor-Lewis procedure was carried out as described previously. [6] Under general anesthesia by tracheal cannula, the supine position was adopted for the dissociation of the stomach and lymphadenectomy of the abdominal lymph nodes via a median incision in the upper abdomen. The patients were assigned to the left lateral position for dissociation of the thoracic esophagus to clear the way for access to the thoracic lymph nodes via a posterolateral incision in the 5th intercostal space.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation